Foreign minors at risk of statelessness: analysis of cases on the right to identity and nationality - Barbero, Iker (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2026)
This article focuses on the so-called “invisible migrant childhood” or “at risk of statelessness”, to refer to those children who have been born in the migratory journey of their mothers and who, due to multiple circumstances, their birth has not been officially registered in any country. This non-registration results in the practical impossibility of determining the nationality, while it also generates difficulties in accessing basic fundamental rights such as education or health. Given the novelty of this phenomenon, the Administrations lack of tools based on domestic law to intervene in accordance with the “best interests of the child”. As the cases analysed in this study show, while international treaties and conventions (such as the Convention on the Rights of the Child) are also part of the Spanish legal system, they can be used, not as mere interpretative criteria but as direct application in the legal arguments of administrative and judicial decisions.